Multivariate analysis of yield and quality traits in sweet potato genotypes (Ipomoea batatas L.) - Alam, Z.; Akter, S.; Khan, M.a.H.; Amin, M.N.; Karim, M.R.; Rahman, M.H.S.; Rashid, M.H.; Rahman, M.A.; Mokarroma, N.; Sabuz, A.A.; Alam, M.J.; Roy, T.K.; et al. (Elsevier, 2024)
Improving sweet potato traits and genotype selection based on specific traits of interest is crucial to motivate farmers and rural households to enhance their livelihoods by increasing income and improving nutritional intake. This research offers a thorough analysis of genotype selection guidelines considering multiple traits of sweet potatoes, including vine length (VL), average root length (ARL), average root diameter (ARD), marketable storage root number (MRN), marketable storage root yield (MRY), non-marketable root number (NMRN), nonmarketable root weight (NMRW), dry weight of root (DW), beta-carotene content (BC), vitamin C content (VC), starch content (ST), total sugar content (TS), total soluble solid (TSS), and titratable acidity (ACD). The findings showed that the genotype Moz1.15 achieved the highest MRY at 46.46 t/ha, H5.ej.10 displayed the top BC level at 48.94 mg/100 g, and Moz1.9 had the highest VC (23.89 mg/100 g). Furthermore, there was a significant positive correlation between VL and DW, TSS, ST, TS, and VC. Additionally, ARL, ARD, and MRN showed significant positive correlations with MRY. The principal component analysis (PCA) biplot further confirmed how traits were connected with each other. There were four separate clusters of genotypes found, each having its specific significant trait representation. The distance between these clusters ranged from 21.79 to 54.13, while within each cluster, the distances varied from 0 to 17.45. The factor analysis using the multi-trait genotypeideotype distance index (MGIDI) showed that sweet potato traits played a substantial role in three distinct factors during both growing seasons (2020-21 and 2021-22). This allowed for the selection of genotypes capable of achieving favorable genetic gains ranging from 1.86% to 75.4%, alongside a broad-sense heritability (h2b) spanning from 64.9% to 99.8%. Through the application of the MGIDI index, a number of potential genotypes were identified, among which BARI Mistialu-12 and H9.7.12 stood out as consistently chosen across both years. These promising genotypes exhibited high performance while displaying their strengths and weaknesses in terms of their contributions to the identified factors. This thorough research offers valuable insights into the complex relationship between different traits in sweet potatoes and how genotype selection based on a multi-trait index can significantly assist in shaping upcoming breeding and cultivation strategies.